2017
DOI: 10.1002/adem.201600879
|View full text |Cite
|
Sign up to set email alerts
|

A Cycle‐Etching Approach Toward the Fabrication of Superamphiphobic Stainless Steel Surfaces With Excellent Anticorrosion Properties

Abstract: In this paper, a facile approach is developed for preparing superamphiphobic surfaces with excellent anticorrosion properties on 304 stainless steel (SS) substrates. This proposed methodology involves fabrication of micro/nano-scale binary structures on SS substrates by a cycle-etching approach (cycles of hydrofluoric acid etching and ultrasonic cleaning), and final fluoroalkylsilane modification. Wettability measurements reveal that the fabricated SS surfaces become super-repellent toward water and peanut oil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 49 publications
(46 reference statements)
0
10
0
Order By: Relevance
“…Natural competition and selection have donated many interesting abilities to animals and plants in responding and adapting to the changes of environment around them. , For example, although living in a muddy environment, lotus leaves never get dirty owing to their extraordinary water repellency and unique self-cleaning property. Inspired by the lotus effect, , superhydrophobic coatings featured by high contact angles (CA > 150°) and low sliding angles (SA) of water have drawn significant attention. Superhydrophobic coatings are very promising materials in various areas including self-cleaning, , oil/water separation, , anti-icing, anticorrosion, and anti-biofouling. , Various approaches have been developed to fabricate superhydrophobic coatings, for example, sol–gel, chemical vapor deposition, electrospinning, and chemical etching. However, their application is restricted by some main bottlenecks, especially the pollutive preparation methods (e.g., organic solvents and fluorinated compounds) and poor mechanical stability.…”
Section: Introductionmentioning
confidence: 99%
“…Natural competition and selection have donated many interesting abilities to animals and plants in responding and adapting to the changes of environment around them. , For example, although living in a muddy environment, lotus leaves never get dirty owing to their extraordinary water repellency and unique self-cleaning property. Inspired by the lotus effect, , superhydrophobic coatings featured by high contact angles (CA > 150°) and low sliding angles (SA) of water have drawn significant attention. Superhydrophobic coatings are very promising materials in various areas including self-cleaning, , oil/water separation, , anti-icing, anticorrosion, and anti-biofouling. , Various approaches have been developed to fabricate superhydrophobic coatings, for example, sol–gel, chemical vapor deposition, electrospinning, and chemical etching. However, their application is restricted by some main bottlenecks, especially the pollutive preparation methods (e.g., organic solvents and fluorinated compounds) and poor mechanical stability.…”
Section: Introductionmentioning
confidence: 99%
“…[6,7] Moreover superhydrophobic surfaces have shown efficient response in various applications including self-cleaning, bio-fouling control, and corrosion protection in addition to oil-water separation due to their water-repellent characteristics. [8][9][10][11][12][13] Literature provides a good understanding of superhydrophobic phenomenon as mimicked by creating rough micrometer and nanometer scale hierarchical structures with low surface energy. [14][15][16]25,26] Hence, a variety of nanomaterials are used to generate hierarchical surface roughness necessary for superhydrophobic properties; some of these include nanodiamonds, silica, iron oxide, titania, alumina, carbon soot, and carbon nanotubes.…”
Section: Introductionmentioning
confidence: 99%
“…Before the structure surface of springtails was found, researchers have already begun to design re-entrant textures to form functional surface material and predict wetting properties by changing structural parameters. Recently, researchers further confirmed that the essential feature of texture surfaces relies on the re-entrant structure that is similar to the springtail’s skin. The surface material with re-entrant texture has many potential applications, including self-cleaning, liquid transportation, , drag reduction, , corrosion prevention, etc. Therefore, various approaches have been proposed to fabricate re-entrant structure-based surface for functional material. , The mainstream processing method is based on conventional lithography and etching, but these processes require additional masks, and the fabricated structures cannot be flexibly adjusted.…”
Section: Introductionmentioning
confidence: 99%